Effects of micro-credit in the quality of life of the entrepreneurs (2013)
This test analyses the effect of microcredit in improving the quality of life of micro-entrepreneurs, being the only means of inclusive finance in vulnerable populations in order to reduce poverty. To which begins with a brief historical review of the microcredit, then analyzes the regulatory structure governing this activity in the country, in order to carry out a qualitative analysis of the effect of this on the quality of life of micro-entrepreneurs, under the understanding of a subjective notion valued from different edges. This essay intends to create a point of view, starting from the full knowledge of micro-entrepreneurs and the satisfaction of their needs, with emphasis on the responsibility that should assume the State, the private sector and institutions micro-credit operators to create an instrument that effectively development generator